Development of a Functional Yogurt Containing Probiotics and Phenolic Compounds of Coffee Encapsulated in Alginate Beads - Aurora Viridiana Toalá-Gómez; Claudia Mendoza-Avendaño; Maria Celina Lujan-Hidalgo; Miguel Angel Ruiz-Cabrera; Alicia Grajales-Lagunes; Enna Berenice Estudillo-Diaz; Lucia Maria Cristina Ventura Canseco; Gabriela Palacios-Pola; Miguel Abud-Archila (Fermentation, 2025)
Probiotics and phenolic compounds provide benefits to humans when they are consumed in adequate amounts. However, these materials are not very stable and can easily be degraded during processing and storage; so, they must be protected. This study evaluated the encapsulation of Lactiplantibacillus fabifermentans BAL-27 ITTG and phenolic compounds from coffee husks via alginate beads. The research considered variables such as alginate concentration (1.5% and 3%), crosslinking time (8 and 20 min), and the inclusion of chitosan. A 23 factorial design was employed, and the effects were analyzed via ANOVA (p < 0.05). The encapsulation efficiency of the probiotic exceeded 80%, and its viability following gastrointestinal simulation ranged from 73.65% to 85.34%. The phenolic compounds achieved encapsulation efficiencies of up to 20%. In yogurt, the alginate beads maintained probiotic viability at approximately 9 Log10 CFU/g and preserved the stability of the antioxidant compounds over 28 days. Moreover, the incorporation of beads did not adversely affect the physicochemical properties or sensory acceptance of the yogurt, supporting their potential application in functional foods.